Analysis of Plant Species in Xiqing Country Park, Tianjin. Issue 1 (November 2020) - Gui, Yu; Huang, Handa; Yang, Jinghui
Abstract: To explore the plant species and its composition in Xiqing country park in Tianjin, this paper investigated the species, families, genera and community structure of trees, shrubs, ground cover, aquatic and hygrophytes in this park by combining field investigation with indoor analysis. The results showed that there were 51 species of plants in 24 families, 41 genera, in which there were 8 families, 12 genera, 21 species of trees, and 5 families, 7 genera and 7 species of shrubs, 10 families 17 genera 18 species of ground cover plant, 4 families 5 genera 5 species of aquatic hygrophyte in the park. More species of trees, less species of shrubs and ground cover were in the park, and Aquatic plants were the least. There were arbor artificial community, wild herbaceous community and artificial herbaceous community. This paper discussed the characteristics and problems of plant configuration in Xiqing country park, and corresponding suggestions were put forward.